Iraqi EFL Learners' Recognition and Production of English Derivational Suffixes - ahmed, mubdir shihab (Al-Adab Journal, 2020)
This study aims at testing the Iraqi EFL learners' recognition and production of the derivational suffixes in English and namely, noun, verb, adjective, and adverb. It is hypothesized that the Iraqi EFL learners find difficulty in forming new correct parts of speech from the roots due to their unsureness of the suitable derivational suffixes. Also, they tend to use derivational suffixes with different parts of speech depending on different factors like guessing and generalization. The sample of this study is fourth-year Iraqi students of the Department of English/ College of Education Ibn Rushd/ Universitry of Baghdad of the academic year (2014-2015). To achieve the aim of this study a test, which comprises two questions, has been constructed. A multiple-choice question at the recognition level and a completion question at the production level are constructed. The findings of the test show that Iraqi EFL university learners face difficulty in recognizing and producing the derivational suffixes of different parts of speech. In the light of the results, some conclusions have been drawn and a number of recommendations and suggestions have been presented.